Metabolic Aspects of Neuron-Oligodendrocyte-Astrocyte Interactions - Amaral, Ana I.; Meisingset, Tore W.; Kotter, Mark R.; Sonnewald, Ursula (Frontiers in Endocrinology, 2013)
Whereas astrocytes have been in the limelight on the metabolic glucose interaction scene for a while, oligodendrocytes are still waiting for a place. We would like to call oligodendrocyte interaction with astrocytes and neurons: NOA (neuron – oligodendrocyte – astrocyte) interactions. One of the reasons to find out more about oligodendrocyte interaction with neurons and astrocytes is to detect markers of healthy oligodendrocyte metabolism, to be used in diagnosis and treatment assessment in diseases such as Perinatal hypoxic-ischemic encephalopathy and multiple sclerosis in which oligodendrocyte function is impaired, possibly due to glutamate toxicity. Glutamate receptors are expressed in oligodendrocytes and also vesicular glutamate release in the white matter has received considerable attention. It is also important to establish if the glial precursor cells recruited to damaged areas are developing oligodendrocyte characteristics or those of astrocytes. Thus, it is important to study astrocytes and oligodendrocytes separately to be able to differentiate between them. This is of particular importance in the white matter where the number of oligodendrocytes is considerable. The present review summarizes the not very extensive information published on glucose metabolism in oligodendrocytes in an attempt to stimulate research into this important field.